Biologi Perbungaan Keladi Tikus (Typhonium flageliforme): Seludang Bunga Menghambat Penyerbukan? - Rachman, Erlin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
A study on the flower biology on keladi tikus (T. flageliforme) was conducted to uncover if its spathe inhibitspollination from external pollen resources and causes very low fruit set. The spathe box closely envelopes thesexually vital properties of its inflorenscence. Observation was carried out on some plant clump grown on someuniform potting. A hole was made with scalpel about 4 x 5 mm on a side of the spathe to break its isolation. Somenearer flowers in same clump were left without treatment at all as experimental control. Parameter observed waspresence or absence of seeded fruit setting on spadix. The study result showed that almost all treated flowerspadix per potting, set seeded fruits significantly higher (63, 69 ± 37, 64) than that of controls (3, 57 ± 9, 45) so it isa great possibility that spathe can inhibit partially fruit set. Flower structure and its reproductive phenology werealso described.